Survival Strategies and Color Preferences of Mandarin Fish (Siniperca chuatsi) and Mud Carp (Cirrhinus molitorella): Implications for Aquaculture - Miao Xiang; Nian Wei; Haoran Liu; Mulan Liao; Zihao Meng; Xuemei Li (Animals)
This study evaluated the habitat coloration preferences of Siniperca chuatsi and Cirrhinus molitorella in both solitary (n = 1) and group (n = 3) settings across six colors. The results indicated that both individual and group S. chuatsi spent the majority of their time in and made frequent visits to the black area, followed by the blue area. While individual C. molitorella spent the majority of their time and visits in the blue region, groups showed a preference for the blue and white regions. These findings highlight the distinct habitat coloration preferences of S. chuatsi and C. molitorella in different group states, suggesting that habitat coloration has an important effect on fish behavior and environmental adaptation. From a behavioral ecology perspective, these preferences may be closely related to the survival strategies of fish. Notably, C. molitorella’s strong preference for blue and white backgrounds may reflect anti-predator behavior, helping C. molitorella avoid predators, such as S. chuatsi, in natural environments, thereby improving its chances of survival. This study provides a scientific basis for optimizing aquaculture environments, emphasizing the importance of considering habitat coloration and substrate type in designing environments to enhance fish welfare.